2018
DOI: 10.1371/journal.pone.0199834
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic diversity, poverty and social trust in Germany: Evidence from a behavioral measure of trust

Abstract: Several scholars have concluded that ethnic diversity has negative consequences for social trust. However, recent research has called into question whether ethnic diversity per se has detrimental effects, or whether lower levels of trust in diverse communities simply reflect a higher concentration of less trusting groups, such as poor people, minorities, or immigrants. Drawing upon a nationally representative sample of the German population (GSOEP), we make two contributions to this debate. First, we examine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 63 publications
0
25
0
3
Order By: Relevance
“…Investing to help a stranger has this incentive structure, where any downstream benefits of the helpful action are typically delayed and/or uncertain [38,81,82]. The effect of reduced income or lowered neighbourhood quality on the tendency to help a stranger could also be mediated by reduced social capital and generalized trust [83][84][85][86]. For example, a natural experiment in Russia found that a 10% decrease in average national income following the 2009 recession was associated with a 5% decrease in social trust [87].…”
Section: Discussionmentioning
confidence: 99%
“…Investing to help a stranger has this incentive structure, where any downstream benefits of the helpful action are typically delayed and/or uncertain [38,81,82]. The effect of reduced income or lowered neighbourhood quality on the tendency to help a stranger could also be mediated by reduced social capital and generalized trust [83][84][85][86]. For example, a natural experiment in Russia found that a 10% decrease in average national income following the 2009 recession was associated with a 5% decrease in social trust [87].…”
Section: Discussionmentioning
confidence: 99%
“…An ecologically valid measure of trust involving costly behavior already exists in the domain of measuring trust between strangers. In the well-known "classical" trust game, the player in the role of investor can transfer a share of an initial monetary endowment to an anonymous partner, the trustee ( [8,11]; for recent research on trust behavior also see [17,18]). If the investor transfers money, the total amount available to be shared between the two players increases.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the activity of university graduates in communities, big data play a significant role, which makes it possible to study information about human behavior in real time, who, where, with whom interacts, including the study of social "contamination". Such data allow observing online activity through social connections of patterns of attitudes, emotions (Johanna Gereke, Max Schaub, Delia Baldassarri [9].…”
Section: Introductionmentioning
confidence: 99%